2018
DOI: 10.1186/s12885-018-4348-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of a normal tissue complication probability (NTCP) model for radiation-induced hypothyroidism in nasopharyngeal carcinoma patients

Abstract: BackgroundThe objectives of this study were to build a normal tissue complication probability (NTCP) model of radiation-induced hypothyroidism (RHT) for nasopharyngeal carcinoma (NPC) patients and to compare it with other four published NTCP models to evaluate its efficacy.MethodsMedical notes of 174 NPC patients after radiotherapy were reviewed. Biochemical hypothyroidism was defined as an elevated level of serum thyroid-stimulating hormone (TSH) value with a normal or decreased level of serum free thyroxine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 33 publications
2
43
0
Order By: Relevance
“…Data from previous studies examining the role of chemotherapy on HT development are inconclusive. Some studies have found that concurrent chemotherapy application increased the probability of HT development 8,19,22. In the study from Luo et al .…”
Section: Discussionmentioning
confidence: 97%
“…Data from previous studies examining the role of chemotherapy on HT development are inconclusive. Some studies have found that concurrent chemotherapy application increased the probability of HT development 8,19,22. In the study from Luo et al .…”
Section: Discussionmentioning
confidence: 97%
“…It remains controversial whether sex worsens the adverse effect of radiotherapy-induced HT; many researchers believe that female patients have a higher risk of HT . [19,24,29] Fan et al [16] observed 2.03 times increased HT incidence in women relative to men among 14,893 patients with NPC and 16,105 patients with other head and neck cancers. Yet, others disagree: Bhandare et al [30] reported that HT incidence in female patients was no higher than that in male patients.…”
Section: Hypothyroidism and Other Factorsmentioning
confidence: 99%
“…Wu et al [17] suggested that subclinical HT is strongly correlated with female patients or patients with lower T stage (T 1-2 vs. T 3-4 ). However, Luo et al [29] identified chemotherapy as one of the most predictive factors for radiation-induced HT. In our research, we found that chemotherapy and T stage had no obvious statistically significant relation to the incidence of HT.…”
Section: Hypothyroidism and Other Factorsmentioning
confidence: 99%
“…Therefore, dosimetry parameter depicting both the threshold dose of follicle and the number of influenced follicles will be a promising predictor for HT after RT, and that is the parameter Vx, defined as the percentage of thyroid volume receiving more than a to-be-determined threshold dose, x Gy. However, so far, there is no consensus on such a threshold dose, and the reported threshold dose ranges from 30 to 50 Gy (5)(6)(7)(8)(9)(10)(11). Previous studies have generally selected the best Vx for predicting HT based on multivariate regression analysis (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…However, so far, there is no consensus on such a threshold dose, and the reported threshold dose ranges from 30 to 50 Gy (5)(6)(7)(8)(9)(10)(11). Previous studies have generally selected the best Vx for predicting HT based on multivariate regression analysis (5)(6)(7)(8). However, the reported results are limited by the collinearity of the data caused by their overlap: that is, V 10 would also include V 20 .…”
Section: Introductionmentioning
confidence: 99%